2019
DOI: 10.1371/journal.pbio.3000104
|View full text |Cite
|
Sign up to set email alerts
|

Spliceosomal Prp8 intein at the crossroads of protein and RNA splicing

Abstract: The spliceosome is a large ribonucleoprotein complex that removes introns from pre-mRNAs. At its functional core lies the essential pre-mRNA processing factor 8 (Prp8) protein. Across diverse eukaryotes, this protein cofactor of RNA catalysis harbors a self-splicing element called an intein. Inteins in Prp8 are extremely pervasive and are found at 7 different sites in various species. Here, we focus on the Prp8 intein from Cryptococcus neoformans (Cne), a human fungal pathogen. We solved the crystal structure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 95 publications
1
34
0
Order By: Relevance
“…Zinc inhibits DnaBi1 splicing in the native mycobacterial host. Divalent cations have been shown to influence protein splicing, in some cases binding directly to the intein (21,34,35). Further, it has been shown that DnaBi1 is subject to conditional splicing regulation via the redox state of catalytic cysteines (7).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Zinc inhibits DnaBi1 splicing in the native mycobacterial host. Divalent cations have been shown to influence protein splicing, in some cases binding directly to the intein (21,34,35). Further, it has been shown that DnaBi1 is subject to conditional splicing regulation via the redox state of catalytic cysteines (7).…”
Section: Resultsmentioning
confidence: 99%
“…Inteins are often found in experimentally challenging organisms such as pathogenic bacteria (e.g., M. tuberculosis) (11,25), pathogenic fungi (e.g., Cryptococcus neoformans) (21,35), and extremophilic archaea (e.g., Pyrococcus horikoshii) (9, 10). As a result, studies examining conditional protein splicing (CPS) in the native host have proven difficult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations